LABVIRTUAL—A platform for the teaching of chemical engineering: The use of interactive videos. Issue 5 (28th June 2018) - Granjo, José F.O.; Rasteiro, Maria G.
Abstract: This article focus on the pedagogical tools in LABVIRTUAL (http://labvirtual.eq.uc.pt ), a broad scope virtual platform intended to support the learning at the undergraduate level of Chemical Engineering courses, mainly in Portuguese‐speaking countries. The platform contains fundamentals, case studies, simulators, virtual laboratories, and, recently, interactive videos for the teaching of chemical processes. The significance and impact of LABVIRTUAL are illustrated with an interactive video regarding the characterization of nanoparticles by dynamic light scattering, developed for long‐distance learning and used in the discipline of Technology of Disperse Systems. Furthermore, two questionnaires were prepared to assess the students' response to the interactive video and the use of LABVIRTUAL in general. The results show that the interactive video is effective to prepare the laboratory work and guide the students' self‐regulated study, but needs to be complemented with other pedagogical methods to enhance the learning outcomes. LABVIRTUAL is generally viewed as a valuable learning tool by the students of Separation Processes and Project Design, 3rd and 5th year courses, respectively, of the Masters' degree in Chemical Engineering of the University of Coimbra, due to the synergy of pedagogical tools that complement well the face‐to‐face classroom lectures. This fact also justifies the high number of monthly visits, including from companies that use the platform as a life‐long learning tool.